PENGARUH LUAS LAHAN, MODAL DAN TENAGA KERJA TERHADAP PENDAPATAN PETANI SAYUR DI DESA BATURITI SELAMA PANDEMI COVID-19 - Widiani, Ni Made Nia; Bendesa, I. K. G. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Indonesia is an agrarian country where most of the population works as farmers as well as Baturiti Village, Baturiti District, Tabanan Regency, Bali. Its geographical condition which is in the highlands makes vegetables the most widely grown commodity by farmers in Baturiti Village. Entering the Covid-19 Pandemic, agriculture, especially vegetables, experienced a significant decline. This study aims to analyze the effect of land area, capital and labor on the income of vegetable farmers during the Covid-19 pandemic using an associative quantitative approach. The research location is in Baturiti Village with a total sample of 100 vegetable farmers spread over eight different banjars. The data analysis technique method used is multiple linear regression. The results of the analysis show that land area, capital and labor simultaneously have a significant effect on the income of vegetable farmers in Baturiti Village during the Covid-19 Pandemic. Partially land area has a negative and significant effect on the income of vegetable farmers, while capital and labor partially have a positive and significant effect on the income of vegetable farmers in Baturiti Village during the Covid-19 Pandemic.